NILAI KARAKTER BERSUMBER DARI PANCASILA DENGAN PENDEKATAN EMPATI PADA SISWA SEKOLAH DASAR - Sasmita, Wikan; Suratman, Suratman; Widodo, Agus; Andyastuti, Etty; Nursalim, Nursalim; Pristiani, Yunita Dwi; Wiranata, Irawan Hadi; Fauziah, Hamidah Ulfa; Riswandi, Fitta Nurisma (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Character values sourced from Pancasila with an empathetic approach to elementary school students aim to provide socialization and knowledge as well as its implementation in life in elementary schools, because character values such as religious values, family values, harmony values, populist values, and justice values are important to make Indonesian people have Pancasila character. The method used is a qualitative approach with a type of case study at State Elementary School 3 Kandat, Kediri Regency. The process of collecting data on interviews, observations, and documentation. Analysis technique with conclusions. Validity checks with the presence of researchers and expanded triangulation. The results of the study showed that the increase in changes in attitude patterns and better character of students about character values sourced from Pancasila with an empathetic approach for elementary school students consisted of: 1) religious values (divine values), 2) family values (human values), 3) harmony values (unity values), 4) populist values, 5) justice values. This starts from class VI which will later provide a good example of implementation to classes V and IV.